KEMAMPUAN IBU PRIMIPARA SETELAH DIBERIKAN LATIHAN TEKNIK PERAWATAN TALI PUSAT PADA BAYI DENGAN KASA KERING DI WILAYAH KERJA BPM DINCE SAFRINA RUMBAI - Julimar Julimar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Umbilical cord care is done to prevent the occurrence of infection and accelerate the process of drying and release of the umbilical cord while the good and proper care will cause the impact of the umbilical cord will be lost or loose on day 5 to day-7 without any complications. The purpose of this Final Report is to describe the cognitive and psychomotor abilities of primiparous moms after being given an umbilical cordage care technique with dry gauze in BPM Working Area Dince Safrina Rumbai. This study is a descriptive case study with 1 subject of research and conducted on February 14 until May 9, 2017. This study uses data collection techniques through interviews and observation methods. Data is presented in narrative form. Based on the results of the study showed that subjects had cognitive (knowledge) less (33.3%) about cord care in newborn and psychomotor (ability) increased after the subjects were given information by using leaflets about umbilical cord care and after rope treatment techniques Center with dry gauze. Recommendations for further research are able to develop prior research, and further research on cord care with dry gauze based on the number of different subjects and other factors that can accelerate the release of the umbilical cord.